Lactobacillus casei Strain Shirota Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice by Increasing Taurine-Conjugated Bile Acids and Inhibiting NF-κB Signaling via Stabilization of IκBα - Wong, Wing-Yan; Chan, Brandon Dow; Sham, Tung-Ting; Lee, Magnolia Muk-Lan; Chan, Chi-On; Chau, Chung-Ting; Mok, Daniel Kam-Wah; Kwan, Yiu-Wa; Tai, William Chi-Shing (Frontiers in Nutrition, 2022)
Inflammatory bowel disease (IBD) is a chronic progressive intestinal inflammatory disease, characterized by an altered gut microbiota composition and accompanying alterations in circulatory bile acids. Increasing evidence supports the beneficial effect of probiotics intake on health. Introduction of probiotics to the intestines can modulate gut microbiota composition and in turn regulate the host immune system and modify the inflammatory response. Probiotics can also improve intestinal barrier function and exhibit a positive impact on host physiological and pathological conditions via gut microbiota-derived metabolites. Previous studies have demonstrated that Lactobacillus casei strain Shirota (LcS) treatment could inhibit clinical manifestation of colitis in dextran sulfate sodium (DSS)-induced mice, however, the underlying mechanisms remain unknown. In this study, we employed the DSS-induced acute colitis mouse model to investigate the anti-inflammatory effects of LcS and related mechanisms. Administration of LcS ameliorated the severity of DSS-induced colitis and enhanced intestinal integrity via induction of mucin-2 and occludin expression in colons. Fecal microbiota analysis showed that LcS increased the relative abundance of beneficial bacterial species in colitis mice, whereas the relative abundance of pathobionts were reduced. Additionally, LcS treatment modulated circulating bile acid profiles in colitic mice. In mice treated with LcS, we identified increased levels of primary taurine-conjugated bile acids, including taurocholic acid (TCA) and taurochenodeoxycholic acid (TCDCA). LcS treatment also increased the levels of secondary taurine-conjugated bile acids, including taurodeoxycholic acid (TDCA) and tauroursodeoxycholic acid (TUDCA). Moreover, LcS treatment exhibited a suppressive effect on the hydroxylated primary bile acids α-muricholic acid (α-MCA) and β-muricholic acid (β-MCA). We further demonstrated that LcS treatment suppressed the expression of pro-inflammatory mediators IFN-γ and NO, and increased the expression of the anti-inflammatory mediator IL-10 in mouse colon tissues, potentially as a result of altered bile acid profiles. Mechanistically, we showed that LcS treatment suppressed the activation of NF-κB signaling via stabilization of IκBα. Altogether, we have demonstrated the therapeutic effects of LcS in DSS-induced colitis, providing new insights into its effect on bile acid metabolism and the related anti-inflammatory mechanisms. Our findings provide support for the application of LcS in the treatment of IBD.